Gilda Joyce, psychic investigator / 1 - Allison, Jennifer (Gilda Joyce, 2005)
During the summer before ninth grade, intrepid Gilda Joyce invites herself to the San Francisco mansion of distant cousin Lester Splinter and his thirteen-year-old daughter, where she uses her purported psychic abilities and detective skills to solve the mystery of the mansion's boarded-up tower.